Allergic Comorbidity of Asthma or Wheezing, Allergic Rhinitis, and Eczema: Result From 333 029 Allergic Children in Shanghai, China. Issue 2 (March 2020) - Ji, Heyu; Hu, Yi; Zhang, Ting; Wang, Yizhong; Shen, Li; Wang, Shu; Chen, Min; Wei, Mingyue; Yu, Guangjun
Background: Allergic diseases have become a worldwide public health concern. A defining feature of allergic diseases is they often coexist in children from birth to adolescence. Objective: To investigate the prevalence of comorbid allergic diseases in allergic children in Shanghai, China. Methods: A retrospective study of 333 029 children diagnosed with allergic diseases aged 0 to 12 years (mean age: 3.04 years, 59.3% boys) was conducted using the electronic medical records of Shanghai Children's Hospital from January 2013 to July 2018. Comorbidity of allergic diseases is defined as the coexistence of 2 or 3 following diseases in the same child such as asthma (AS)/wheezing, allergic rhinitis (AR), or eczema (EC). Results: The proportion of children with comorbid allergic diseases was 6.7% (22 351/333 029). Among them, EC + AS/wheezing was the most common (61.3%, 13 711/22 351). Children with a comorbidity had significantly earlier disease onset age than subjects with only 1 disease (2.72 vs 3.06, P  < .05). The serum total immunoglobulin E (tIgE) levels of children with comorbid allergic diseases were higher than those with only 1 disease. In children with a disease onset age of 0 to 9 years, the levels of tIgE for children with AS/wheezing + EC were higher than children with AS/wheezing only or EC only; in children with disease onset age of 2 to 5 and 10 to 12 years, the levels of tIgE for children with AS/wheezing + AR were higher than children with AS/wheezing only or AR only; in children with a disease onset age of 2 to 5 years, the levels of tIgE for children with AR + EC were higher than children with AR only or EC only. Conclusion: Comorbidity of allergic diseases is common in children in Shanghai, China. The onset age of comorbidity is earlier than that of only 1 disease, and the levels of serum tIgE are higher in patients with an allergic comorbidity.